Novos passos em direção à ciência aberta - Brait, Beth; Cruz Pistori, Maria Helena; Lopes-Dugnani, Bruna; Stella, Paulo Rogério; Gontijo Rosa, Carlos (Bakhtiniana. Revista de Estudos do Discurso, 2022)
Editorial 18.1